Child and adolescent injury burden in the eastern mediterranean region: Findings from the Global Burden of Disease 1990-2017 - Al-Hajj, Samar (BMC Public Health, 2020)
BACKGROUND: Child and adolescent injury is one of the leading causes of child death globally with a large proportion occurring in Low- and Middle-Income Countries (LMICs). Similarly, the Eastern Mediterranean Region (EMR) countries borne a heavy burden that largely impact child and adolescent safety and health in the region. We aim to assess child and adolescent injury morbidity and mortality and estimate its burden in the Eastern Mediterranean Region based on findings from the Global Burden of Disease (GBD), Injuries and Risk Factors study 2017. METHODS: Data from the Global Burden of Disease GBD 2017 were used to estimate injury mortality for children aged 0–19, Years of Life Lost (YLLs), Years lived with Disability (YLDs) and Disability Adjusted Life Years (DALYs) by age and sex from 1990 to 2017. RESULTS: In 2017, an estimated 133,117 (95% UI 122,587-143,361) children died in EMR compared to 707,755 (95% UI 674401.6–738,166.6) globally. The highest rate of injury deaths was reported in Syria at 183.7 (95% UI 181.8–185.7) per 100,000 population. The leading cause of injury deaths was self-harm and interpersonal violence followed by transport injury. The primary cause of injury DALYs in EMR in 2017 was self-harm and interpersonal violence with a rate of 1272.95 (95% UI 1228.9 – 1319.2) almost 3-times the global rate. CONCLUSION: Almost 19% of global child injury related deaths occur in the EMR. Concerted efforts should be integrated to inform policies and adopt injury preventive strategies to reduce injury burden and promote child and adolescent health and well-being in EMR countries.